(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The safety of stored data in the cloud is of the utmost significance. There is a lot of room for user data in cloud storage. This technology has proven to be a groundbreaking effort because of its ability to offer cheap, extensive computational storage that users may access from anywhere at any time. By entrusting their data to the cloud, users may take advantage of services that are flexible, efficient, and run smoothly. Once data has been transferred to the cloud, the onus for its administration shifts entirely to the CSP. Data stored in the cloud raises a number of security problems, in addition to the benefits. Data in transit and data at rest are both susceptible to assaults when users move their data to the cloud. Data protection and building confidence in cloud services are now top priorities. Data should be kept in an encrypted or masked format to prevent unauthorised access. One major problem with cloud computing is the lack of assurance around data protection. By integrating obfuscation with steganography, this study reveals a novel and advanced method to strengthen data security. To guarantee confidentiality, the proposed method incorporates obfuscation and steganography techniques. In contrast to steganography, whose main goal is to mask the existence of information, obfuscation primarily seeks to transform data into a different form while simultaneously concealing the original data. Using the Least Significant Bit (LSB) replacement technique, the hidden text may be hidden inside a picture. The results of the experiments show that the proposed method may successfully integrate large amounts of data and generate high-quality stego images.